Co-parasitism by chigger mites (Trombidiformes: Leeuwenhoekiidae) and soft ticks (Ixodida: Argasidae) in Brazilian anurans, with the description of a new Hannemania species - Isabella Pereira Pesenato; Ricardo Bassini-Silva; Pedro Paulo Goulart Taucci; Nadya Carolina Pupin; Murillo Castelo Branco Monho; Giovanna Rafaeli Rezende; Maria Eduarda Barbosa de Souza-Silva; Sebastian Muñoz-Leal; Marcelo B. Labruna; Darci Moraes Barros-Battesti; Fernando de Castro Jacinavicius (Systematic Parasitology, 2026)
Bokermannohyla frogs comprise species distributed across different Brazilian biomes, several of which are currently listed as endangered species. These anurans host a diversity of parasites that may negatively affect their survival. Several tick species of the family Argasidae and chigger mites of the family Leeuwenhoekiidae exhibit host specificity toward this group. Here, we report a case of co-parasitism by argasid ticks and chigger mites in this frog genus collected in the Bahia State, Brazil, and describe a new species of Hannemania, H. diamantinensis sp. nov. Anurans were captured in Chapada Diamantina National Park, and ectoparasites were collected and identified using morphological methods. Ticks were identified as Ornithodoros saraivai , while chigger mites correspond to a new species. This represents the first record of O. saraivai in Bahia State, and the description of a new Hannemania species increases the number of Brazilian known species to eight.

Simultaneous effusive and explosive activity in moderate-magnitude rhyolite eruptions: H2O and hydrogen isotopic investigation of the 1250 CE eruptions in Lipari, Sicily - Sebastian C. Walter; Jonathan M. Castro; Ilya N. Bindeman (Bulletin of Volcanology, 2026)
Three of the most recent rhyolite eruptions in Europe occurred approximately 800 years ago on the island of Lipari, Aeolian Islands, Sicily. These eruptions produced ash and lava deposits that share many of the physical and chemical traits known to exist in hybrid explosive-effusive silicic systems like the Mono Craters and Medicine Lake (USA), in addition to the recently active rhyolite volcanoes Chaitén (2008) and Cordón Caulle (2011), Chile. Here, we present a study on the microtextures, H 2 O concentrations, and δD values of pyroclastic and effusive deposits of three rhyolite eruptions on Lipari (Lami, Forgia Vecchia, and Rocche Rosse). Textural features of obsidian pyroclasts are, within our parameters of analysis, identical among the three centers. The three vents furthermore display overlapping bulk H 2 O concentrations (0.08–1.22 wt.%) that are in turn similar to previous studies on Lipari and other systems. Hydrogen isotope ratios (δD) decrease from −50.9 to −104.9 ‰ as magmatic water drops from 1.22 to 0.08 wt.%. Modeling of these geochemical trends implies that all erupted products degassed along a single coherent trend. This is consistent with a manner of eruption that would have involved simultaneous and repetitive explosive and effusive emission of isotopically heterogeneous gas from a single magma source. Collectively, our observations and analysis point to hybrid effusive-pyroclastic activity and support previous interpretations that Lipari’s three youngest rhyolitic centers were co-eruptive. This, in turn, implies that more than half of the island would have been affected by direct impacts of a single rhyolitic fissure event at ~ 1250 C E.

Trees just go “nuts”: prioritizing carbon allocation to yield in almond trees - Shreya S. Veeravelli; Andrew J. McElrone; Ian R. Wright; Mina Momayyezi; Kyle R. Knipper; Nicolas E. Bambach; Sebastian Castro Bustamante; Andrew J. Gal; Sat Darshan S. Khalsa; Ranjith Karunakaran; Hung T. T. Nguyen; Morgan E. Furze (Planta, 2026)
Main conclusion Almond trees prioritize C to yield rather than stem growth, and their overall lower NSC stores compared to forest trees may have consequences for resilience under environmental variability. Abstract Perennial tree crops store nonstructural carbohydrates (NSCs) as energy reserves that can be used to persist during both predictable periods of reduced activity like dormancy and more unpredictable periods associated with stress. For deciduous tree crops, which lose their leaves at the start of dormancy, the NSC reserves accrued by that time are critically important for fueling respiration but may also influence processes in the following growing season. To quantify the seasonal NSC fluctuation surrounding dormancy and its influence on downstream processes like growth and yield, we conducted a comparative study of four almond varieties in a commercial orchard (California, USA). Sugar and starch concentrations were quantified in branch, stem, and coarse root when entering and exiting dormancy. We then assessed the correlation between these NSC data and metrics of stem growth and yield in the following growing season. We further explored long-term trade-offs between stem growth and yield using historical data from 2017 to 2022. Overall, total NSC concentrations significantly decreased during the dormant season in all organs. We observed a significant positive correlation between branch total NSC concentration when entering dormancy and yield the next year. However, we unexpectedly found that stem total NSC concentrations when entering dormancy were negatively correlated with stem growth the next year, suggesting that stem reserves were primarily used to support wintertime respiration or translocated to other organs. A long-term trade-off between stem growth and yield was evident; as yield increased, basal area increment tended to decrease. Additionally, we found whole-tree NSC storage to be lower in almond trees compared to temperate forest trees, reflecting prioritization to yield over NSC storage. Overall, these findings advance our understanding of crop tree carbon physiology and provide insight into the resilience of different almond cultivars under changing environmental conditions.

A machine learning framework for California vineyard water status monitoring using sUAS Imagery and short-term meteorological data - Rui Gao; Maria Mar Alsina; Alfonso F. Torres-Rua; Lawrence Hipps; William P. Kustas; Martha Anderson; Héctor Nieto; Andrew J. McElrone; Kyle Knipper; Nicolas Bambach Ortiz; Sebastian J. Castro; John H. Prueger; et al. (Irrigation Science, 2026)
Efficient irrigation management is essential for sustainable crop production under increasing temperatures and tightening water supplies. In vineyards, water status significantly influences vine growth, yield, and fruit quality, and deficit irrigation is often used to impose controlled stress while avoiding damaging levels of water limitation. This creates a practical need for routine, field-scale monitoring of vine water status. In this study, we developed an operational machine-learning framework to estimate grapevine leaf water potential (Ψ leaf ) by integrating daytime sUAS thermal imagery with short-term local meteorological information. When all candidate predictors were included, the trained eXtreme Gradient Boosting (XGB) model achieved R 2 = 0.71, RMSE = 0.14 MPa , and bias = − 0.06 MPa on the independent test dataset. A simplified XGB model using a compact predictor set–maximum air temperature in the 24 h prior to flight, air temperature at flight time, their difference, and canopy temperature – achieved R 2 = 0.63, RMSE = 0.16 MPa , and bias = − 0.06 MPa , with performance not significantly different from the full model at α = 0.05. This reduced-feature formulation supports vineyard-scale Ψ leaf estimation and mapping while maintaining strong predictive skill and low computational burden. Our research highlights the potential for broader applicability, particularly for monitoring rapidly developing hot and dry conditions and supporting adaptive water resource management.

Modelling the diurnal cycle of evapotranspiration using remote sensing models – are we there yet? - K. V. Athira; Eswar Rajasekaran; Kukku Sara; Gilles Boulet; William P. Kustas; Rahul Nigam; Bimal K Bhattacharya; Joseph G. Alfieri; John H. Prueger; Maria Mar Alsina; Lawrence E. Hipps; Lynn G. McKee; et al. (International Journal of Remote Sensing, 2025)

Exploring the determinants of bee diversity in tropical urban areas and their implications for conservation - Ingrid N. Gomes; Victor H.D. Silva; Rodrigo B. Gonçalves; Carlos A. Ordónez-Parra; Carolina P. Procópio-Santos; Sebastian O. Queroz; Diego M.P. Castro; João Carlos Pena; Pietro K. Maruyama (Landscape and Urban Planning, 2025)

Participatory mapping of marine ecosystem services in the Cabo de Gata-Níjar Natural Park (Spain) - Gabriela de Abreu; Irene Olivé; Sebastian Villasante; Mónica Expósito-Granados; Pablo Pita; Jone Molina-Urruela; Emilio Fernández; Gonzalo Méndez-Martínez; Antonio J. Castro (Ocean & Coastal Management, 2025)

The utility and applicability of vegetation index-based models for the spatial disaggregation of evapotranspiration - Sangeetharani Munusamy; Eswar Rajasekaran; Dharmendra Saraswat; William P. Kustas; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; John H. Prueger; Joseph G. Alfieri; Maria Mar Alsina (Irrigation Science, 2025)

3D basin modeling of the Lower Saxony Basin, Germany: the role of overpressure in Mesozoic claystones with implications for nuclear waste storage - Leidy Castro-Vera; Garri Gaus; Marlise Colling Cassel; Sebastian Amberg; Ralf Littke (International Journal of Earth Sciences, 2025)
Jurassic and Cretaceous organic-lean claystone formations in the Lower Saxony Basin (LSB), Germany, are considered for nuclear waste storage due to their favorable physical properties. Understanding the burial and thermal history of these formations, including overpressure generation and its impact, is crucial for site selection. Past undetected overpressures may result in erroneous estimation of present-day petrophysical properties. Therefore, this study investigates the evolution and spatial distribution of overpressure in claystones in northern Germany on a rather large scale, focusing on Jurassic and Lower Cretaceous units. Utilizing 3D numerical basin modeling, this study: (i) reconstructs the geodynamic evolution of the LSB, (ii) identifies key mechanisms driving overpressure during burial, (iii) detects areas of high pore-to-lithostatic pressure ratios susceptible to fracturing, and (iv) assesses overpressure’s influence on the evolution of petrophysical properties. Results reveal that during the fastest burial phase, overpressure generation began, primarily driven by disequilibrium compaction coupled with gas generation, peaking around 99 Ma at the basin’s depocenter. During the Late Cretaceous uplift, thousands of meters of sediment were eroded within the basin’s depocenter, and overpressure dissipated. According to the model, absolute overpressures were higher for Jurassic than Cretaceous claystones, but dissipation was slower for Cretaceous claystones leading to relatively higher pore-to-lithostatic pressure ratios during uplift. During overpressure buildup, the porosity reduction slowed due to undercompaction effects, underscoring overpressure’s influence on petrophysical properties. While Pleistocene glaciations caused localized overpressure, they did not impact the petrophysical properties of the assessed units. Glacial-induced erosion, however, is projected to reduce remaining overpressure substantially. Graphical abstract

Validation of the spray drift modeling software AGDISPpro applied to remotely piloted aerial application systems - Sebastian Castro-Tanzi; Michael Winchell; Zhenxu Tang; Milton E. Teske; Glen R. Whitehouse; Brad Fritz; Dan Martin (Science of The Total Environment, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Combining Spatial Downscaling Techniques and Diurnal Temperature Cycle Modelling to Estimate Diurnal Patterns of Land Surface Temperature at Field Scale - Kukku Sara; Eswar Rajasekaran; Rahul Nigam; Bimal K. Bhattacharya; William P. Kustas; Joseph G. Alfieri; John H. Prueger; Maria Mar Alsina; Lawrence E. Hipps; Lynn G. McKee; Andrew J. McElrone; Sebastian J. Castro; et al. (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)

3D basin modeling of the Hils Syncline, Germany: reconstruction of burial and thermal history and implications for petrophysical properties of potential Mesozoic shale host rocks for nuclear waste storage - Leidy Castro-Vera; Sebastian Amberg; Garri Gaus; Katharina Leu; Ralf Littke (International Journal of Earth Sciences, 2024)
Jurassic sedimentary sequences suitable for nuclear waste storage in northern Germany consist of organic-lean claystone and were uplifted to < 100 m depth in the Hils Syncline area (southern Lower Saxony Basin). This Hils Syncline, showcasing a northwestward increase in thermal maturity, facilitates the study of shale petrophysical properties influenced by burial history. This study introduces a 3D-thermally calibrated numerical model of the Hils Syncline area to analyze its geodynamic evolution and maturity variations. It provides new vitrinite reflectance and sonic velocity data for modeling calibration and erosion estimation. The Hils Syncline area has undergone continuous subsidence, interrupted by a Cretaceous uplift documented by an erosional unconformity. During the latest Early Cretaceous, Jurassic rocks underwent maximum burial reaching up to several thousand meters depth and temperatures up to 160 °C in the northwest. The Late Cretaceous inversion caused stronger erosion towards the northwest removing up to 3300 m of sediment compared to about 1300 m in the south, according to vitrinite reflectance-based estimations. Numerical modeling results along the study area indicate decreasing porosity and permeability northwestward with increasing thermal maturity. Porosity and vertical permeability decreased to 5–14% and 2.8 × 10 –23 to 1.5 × 10 –19 m 2 [1 mD = 10 −15 m 2 ], respectively, while vertical thermal conductivity increased to 1.30–2.12 (W/m/K). These trends of porosity/permeability and thermal conductivity with burial align with sonic velocity and published experimental porosity data, except for the thermally most mature region (Haddessen). This anomaly is tentatively attributed here to localized overpressure generation in the Posidonia Shale during maximum burial, affecting both the underlying Pliensbachian and overlying Doggerian units. Graphical abstract 3D numerical model of the Hils Syncline and surrounding area revealing that a northwestward increase in maximum burial resulted in higher temperatures and varying maturity levels. While most locations align well with calibration data (i.e. measured vitrinite reflectance and porosity), discrepancies arise in the Haddessen/Bensen area. The mismatch between porosity, vitrinite reflectance, and sonic velocity response indicates local overpressure in the northernmost region mainly during the Cretaceous. It was likely caused by gas generation in the Posidonia Shale affecting nearby Lower and Middle Jurassic units.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A comparative analysis of OpenET for evaluating evapotranspiration in California almond orchards - Kyle Knipper; Martha Anderson; Nicolas Bambach; Forrest Melton; Zac Ellis; Yun Yang; John Volk; Andrew J. McElrone; William Kustas; Matthew Roby; Will Carrara; Sebastian Castro; et al. (Agricultural and Forest Meteorology, 2024)

Understanding socioecological interaction networks in Marine Protected Areas to inform management - Silvia de Juan; Andres Ospina-Alvarez; Antonio J. Castro; Emilio Fernández; Gonzalo Méndez-Martínez; Jone Molina; Pablo Pita; Ana Ruiz-Frau; Gabriela de Abreu; Sebastian Villasante (Ocean & Coastal Management, 2023)

Ultrasound-assisted enzymatic synthesis of galacto-oligosaccharides using native whey with two commercial β-galactosidases: Aspergillus oryzae and Kluyveromyces var lactis - Andrés Córdova; Carolina Astudillo-Castro; Paola Henriquez; Natalia Manriquez; Helena Nuñez; Cecilia Guerrero; Dafne Álvarez; Carla Aburto; Vinka Carrasco; Sebastian Oñate; Luciana Lehuedé (Food Chemistry, 2023)

Effects of meteorological and land surface modeling uncertainty on errors in winegrape ET calculated with SIMS - Conor T. Doherty; Lee F. Johnson; John Volk; Meagan S. Mauter; Nicolas Bambach; Andrew J. McElrone; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Sebastian J. Castro; Maria Mar Alsina; William P. Kustas; et al. (Irrigation Science, 2022)
Characterization of model errors is important when applying satellite-driven evapotranspiration (ET) models to water resource management problems. This study examines how uncertainty in meteorological forcing data and land surface modeling propagate through to errors in final ET data calculated using the Satellite Irrigation Management Support (SIMS) model, a computationally efficient ET model driven with satellite surface reflectance values. The model is applied to three instrumented winegrape vineyards over the 2017–2020 time period and the spatial and temporal variation in errors are analyzed. We illustrate how meteorological data inputs can introduce biases that vary in space and at seasonal timescales, but that can persist from year to year. We also observe that errors in SIMS estimates of land surface conductance can have a particularly strong dependence on time of year. Overall, meteorological inputs introduced RMSE of 0.33–0.65 mm/day (7–27%) across sites, while SIMS introduced RMSE of 0.55–0.83 mm/day (19–24%). The relative error contribution from meteorological inputs versus SIMS varied across sites; errors from SIMS were larger at one site, errors from meteorological inputs were larger at a second site, and the error contributions were of equal magnitude at the third site. The similar magnitude of error contributions is significant given that many satellite-driven ET models differ in their approaches to estimating land surface conductance, but often rely on similar or identical meteorological forcing data. The finding is particularly notable given that SIMS makes assumptions about the land surface (no soil evaporation or plant water stress) that do not always hold in practice. The results of this study show that improving SIMS by eliminating these assumptions would result in meteorological inputs dominating the error budget of the model on the whole. This finding underscores the need for further work on characterizing spatial uncertainty in the meteorological forcing of ET.

Improving the spatiotemporal resolution of remotely sensed ET information for water management through Landsat, Sentinel-2, ECOSTRESS and VIIRS data fusion - Jie Xue; Martha C. Anderson; Feng Gao; Christopher Hain; Kyle R. Knipper; Yun Yang; William P. Kustas; Yang Yang; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; Joseph G. Alfieri; et al. (Irrigation Science, 2022)
Robust information on consumptive water use (evapotranspiration, ET) derived from remote sensing can significantly benefit water decision-making in agriculture, informing irrigation schedules and water management plans over extended regions. To be of optimal utility for operational usage, these remote sensing ET data should be generated at the sub-field spatial resolution and daily-to-weekly timesteps commensurate with the scales of water management activities. However, current methods for field-scale ET retrieval based on thermal infrared (TIR) imaging, a valuable diagnostic of canopy stress and surface moisture status, are limited by the temporal revisit of available medium-resolution (100 m or finer) thermal satellite sensors. This study investigates the efficacy of a data fusion method for combining information from multiple medium-resolution sensors toward generating high spatiotemporal resolution ET products for water management. TIR data from Landsat and ECOSTRESS (both at ~ 100-m native resolution), and VIIRS (375-m native) are sharpened to a common 30-m grid using surface reflectance data from the Harmonized Landsat-Sentinel dataset. Periodic 30-m ET retrievals from these combined thermal data sources are fused with daily retrievals from unsharpened VIIRS to generate daily, 30-m ET image timeseries. The accuracy of this mapping method is tested over several irrigated cropping systems in the Central Valley of California in comparison with flux tower observations, including measurements over irrigated vineyards collected in the GRAPEX campaign. Results demonstrate the operational value added by the augmented TIR sensor suite compared to Landsat alone, in terms of capturing daily ET variability and reduced latency for real-time applications. The method also provides means for incorporating new sources of imaging from future planned thermal missions, further improving our ability to map rapid changes in crop water use at field scales.

Evaluating different metrics from the thermal-based two-source energy balance model for monitoring grapevine water stress - Héctor Nieto; María Mar Alsina; William P. Kustas; Omar García-Tejera; Fan Chen; Nicolas Bambach; Feng Gao; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Lynn G. McKee; Einara Zahn; et al. (Irrigation Science, 2022)
Precision irrigation management requires operational monitoring of crop water status. However, there is still some controversy on how to account for crop water stress. To address this question, several physiological, several physiological metrics have been proposed, such as the leaf/stem water potentials, stomatal conductance, or sap flow. On the other hand, thermal remote sensing has been shown to be a promising tool for efficiently evaluating crop stress at adequate spatial and temporal scales, via the Crop Water Stress Index (CWSI), one of the most common indices used for assessing plant stress. CWSI relates the actual crop evapotranspiration ET (related to the canopy radiometric temperature) to the potential ET (or minimum crop temperature). However, remotely sensed surface temperature from satellite sensors includes a mixture of plant canopy and soil/substrate temperatures, while what is required for accurate crop stress detection is more related to canopy metrics, such as transpiration, as the latter one avoids the influence of soil/substrate in determining crop water status or stress. The Two-Source Energy Balance (TSEB) model is one of the most widely used and robust evapotranspiration model for remote sensing. It has the capability of partitioning ET into the crop transpiration and soil evaporation components, which is required for accurate crop water stress estimates. This study aims at evaluating different TSEB metrics related to its retrievals of actual ET, transpiration and stomatal conductance, to track crop water stress in a vineyard in California, part of the GRAPEX experiment. Four eddy covariance towers were deployed in a Variable Rate Irrigation system in a Merlot vineyard that was subject to different stress periods. In addition, root-zone soil moisture, stomatal conductance and leaf/stem water potential were collected as proxy for in situ crop water stress. Results showed that the most robust variable for tracking water stress was the TSEB derived leaf stomatal conductance, with the strongest correlation with both the measured root-zone soil moisture and stomatal conductance gas exchange measurements. In addition, these metrics showed a better ability in tracking stress when the observations are taken early after noon.

Application of the vineyard data assimilation (VIDA) system to vineyard root-zone soil moisture monitoring in the California Central Valley - Fan Chen; Fangni Lei; Kyle Knipper; Feng Gao; Lynn McKee; Maria del Mar Alsina; Joseph Alfieri; Martha Anderson; Nicolas Bambach; Sebastian J. Castro; Andrew J. McElrone; Karrin Alstad; et al. (Irrigation Science, 2022)

Application of a remote-sensing three-source energy balance model to improve evapotranspiration partitioning in vineyards - Vicente Burchard-Levine; Héctor Nieto; William P. Kustas; Feng Gao; Joseph G. Alfieri; John H. Prueger; Lawrence E. Hipps; Nicolas Bambach-Ortiz; Andrew J. McElrone; Sebastian J. Castro; Maria Mar Alsina; Lynn G. McKee; et al. (Irrigation Science, 2022)
Improved accuracy of evapotranspiration (ET) estimation, including its partitioning between transpiration (T) and surface evaporation (E), is key to monitor agricultural water use in vineyards, especially to enhance water use efficiency in semi-arid regions such as California, USA. Remote-sensing methods have shown great utility in retrieving ET from surface energy balance models based on thermal infrared data. Notably, the two-source energy balance (TSEB) has been widely and robustly applied in numerous landscapes, including vineyards. However, vineyards add an additional complexity where the landscape is essentially made up of two distinct zones: the grapevine and the interrow, which is often seasonally covered by an herbaceous cover crop. Therefore, it becomes more complex to disentangle the various contributions of the different vegetation elements to total ET, especially through TSEB, which assumes a single vegetation source over a soil layer. As such, a remote-sensing-based three-source energy balance (3SEB) model, which essentially adds a vegetation source to TSEB, was applied in an experimental vineyard located in California’s Central Valley to investigate whether it improves the depiction of the grapevine-interrow system. The model was applied in four different blocks in 2019 and 2020, where each block had an eddy-covariance (EC) tower collecting continuous flux, radiometric, and meteorological measurements. 3SEB’s latent and sensible heat flux retrievals were accurate with an overall RMSD ~ 50 W/m 2 compared to EC measurements. 3SEB improved upon TSEB simulations, with the largest differences being concentrated in the spring season, when there is greater mixing between grapevine foliage and the cover crop. Additionally, 3SEB’s modeled ET partitioning (T/ET) compared well against an EC T/ET retrieval method, being only slightly underestimated. Overall, these promising results indicate 3SEB can be of great utility to vineyard irrigation management, especially to improve T/ET estimations and to quantify the contribution of the cover crop to ET. Improved knowledge of T/ET can enhance grapevine water stress detection to support irrigation and water resource management.

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Experimental Study of the Influence of Drawbell Geometry on Hang-Ups in Cave Mine Applications - Raúl Castro; Sebastian López; René Gómez; Sebastian Ortiz; Nicolas Carreño (Rock Mechanics and Rock Engineering, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Morphological correlates of sex differences in acoustic startle response and prepulse inhibition through projections from locus coeruleus to cochlear root neurons - Sebastian Hormigo; Ricardo Gómez-Nieto; Consuelo Sancho; Javier Herrero-Turrión; Juan Carro; Dolores E. López; José de Anchieta de Castro e Horta-Júnior (Brain Structure and Function, 2017)

Migratory preferences of humpback whales between feeding and breeding grounds in the eastern South Pacific - Jorge Acevedo; Anelio Aguayo‐Lobo; Judith Allen; Natalia Botero‐Acosta; Juan Capella; Cristina Castro; Luciano Dalla Rosa; Judith Denkinger; Fernando Félix; Lilian Flórez‐González; Frank Garita; Héctor M. Guzmán; et al. (Marine Mammal Science, 2017)
Latitudinal preferences within the breeding range have been suggested for Breeding Stock G humpback whales that summer in different feeding areas of the eastern South Pacific. To address this hypothesis, humpback whales photo‐identified from the Antarctic Peninsula and the Fueguian Archipelago (southern Chile) were compared with whales photo‐identified from lower latitudes extending from northern Peru to Costa Rica. This comparison was performed over a time span that includes 18 austral seasons. A total of 238 whales identified from the Antarctic Peninsula and 25 whales from the Fueguian Archipelago were among those photo‐identified at the breeding grounds. Our findings showed that humpback whales from each feeding area were resighted unevenly across the breeding grounds, which suggests a degree of spatial structuring in the migratory pathway. Humpback whales that feed at the Antarctic Peninsula were more likely to migrate to the southern breeding range between northern Peru and Colombia, whereas whales that feed at the Fueguian Archipelago were more likely to be found in the northern range of the breeding ground off Panama. Further photo‐identification efforts and genetic sampling from poorly sampled or unsampled areas are recommended to confirm these reported connectivity patterns.

Effect of temperature on the morphometric development of eggs in the prawn Macrobrachium americanum (Caridea: Palaemonidae) and larval success under experimental conditions - Juan Carlos Sainz-Hernández; Jesús Arturo Fierro-Coronado; Jazmin Asusena Aguiñaga-Cruz; Luis Daniel García-Rodríguez; John Sebastian Barraza-López; Apolinar Santamaría-Miranda; Juan Pablo Apún-Molina; Claudia Castro-Martínez (Invertebrate Reproduction & Development, 2016)

Home gardens: an assessment of their biodiversity and potential contribution to conservation of threatened species and crop wild relatives in Benin - Valère Kolawolé Salako; Belarmain Fandohan; Barthélémy Kassa; Achille Ephrem Assogbadjo; Alix Franck Rodrigue Idohou; Rodrigue Castro Gbedomon; Sebastian Chakeredza; Mohammad Ehsan Dulloo; Romain Glele Kakaï (Genetic Resources and Crop Evolution, 2014)

Influence of errors in coordinate transformation due to uncertainties of the design matrix - Henry Montecino Castro; Sebastian Santibanez; Sílvio Rogério Correia de Freitas (Applied Geomatics, 2013)

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile - Jonathan M. Castro; C. Ian Schipper; Sebastian P. Mueller; A. S. Militzer; Alvaro Amigo; Carolina Silva Parejas; Dorrit Jacob (Bulletin of Volcanology, 2013)

Schwere Gold-Dermatitis bei Orosanil-Behandlung einer Lungentuberkulösen - M. sebastian Herrador; L. Castro García (Archives of Toxicology, 1936)